Preparation method of composite binder for silicon-based negative electrode, negative electrode plate and lithium battery

By preparing a composite adhesive with a three-dimensional crosslinking network structure, the problem of poor adhesive force and tensile strength in the prior art is solved, and an effective buffering of the volume expansion of the silicon-based negative electrode is achieved to ensure the improvement of electrode integrity and battery performance.

CN119823680APending Publication Date: 2025-04-15GREE ALTAIRNANO NEW ENERGY INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411754252.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, the adhesion and tensile strength of the adhesive agent are poor, resulting in the inability to effectively buffer the volume expansion of the silicon-based negative electrode, affecting the integrity of the electrode and the performance of the battery.

Method used

By adding an initiator dropwise to the acrylamide solution in an inert atmosphere, a mixed aqueous solution of polyacrylamide was obtained, and a supplementary precipitation agent was added to the mixed aqueous solution to obtain a polyacrylamide powder. The polyacrylamide powder is dissolved into the first solvent, tannin acid is added to the intermediate solution, and stirred under ice bath conditions to form a composite binder with a three-dimensional crosslinking network structure.

Benefits of technology

The prepared composite adhesive has excellent adhesion and high tensile properties, which can effectively adapt to the volume expansion of the silicon-based negative electrode, ensure the integrity of the electrode, and improve the performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823680A_ABST
    Figure CN119823680A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a composite binder for a silicon-based negative electrode, a negative electrode plate and a lithium battery. The preparation method comprises the following steps: dropwise adding an initiator into an acrylamide solution in an inert atmosphere to obtain a mixed aqueous solution of polyacrylamide; adding a precipitation aid into the mixed aqueous solution, and sequentially drying and grinding the precipitated solid to obtain polyacrylamide powder; the preparation method comprises the following steps: dissolving polyacrylamide powder into a first solvent to obtain an intermediate solution, adding tannic acid into the intermediate solution, and stirring for a certain time under an ice bath condition to obtain the composite binder with a three-dimensional cross-linked network structure. The technical problem that the volume expansion of the silicon-based negative electrode cannot be well buffered due to poor adhesive force and tensile strength of an adhesive in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of binder preparation, and in particular to a silicon-carbon composite material and a preparation method thereof, a negative electrode sheet, and a lithium battery. Background Art

[0002] Lithium-ion batteries are used as an efficient energy storage device due to their high energy density, long cycle life, good rate performance, high operating voltage and safety, and are widely used in portable electronic devices, electric vehicles, hospitals and other fields.

[0003] As an indispensable auxiliary material in the battery, the binder is a bridge connecting the active material particles, the conductive agent and the current collector. In the prior art, polyacrylamide is used as a binder in negative electrodes such as silicon or silicon carbon, and has achieved relatively ideal performance. On the one hand, it can effectively alleviate the expansion of the electrode and improve the stability of the conductive network inside the battery, thereby ensuring the integrity of the electrode. On the other hand, an artificial solid electrolyte layer (SEI) can be formed on the surface of the electrode to ensure that the electrode will not be corroded by the electrolyte.

[0004] Polyacrylamide as a binder has the following shortcomings: Due to viscosity and tension, it is difficult to evenly mix polyacrylamide with active materials and conductive carbon and to coat it normally on the current collector, which cannot ensure the normal use of the electrode.

[0005] Currently, no effective solution has been proposed to the above problems. Summary of the invention

[0006] The embodiments of the present invention provide a method for preparing a composite binder for a silicon-based negative electrode, a negative electrode sheet, and a lithium battery to solve the technical problem in the prior art that the volume expansion of the silicon-based negative electrode cannot be well buffered due to poor adhesion and tensile strength of the binder.

[0007] According to one aspect of an embodiment of the present invention, a method for preparing a composite binder for a silicon-based negative electrode is provided, and the preparation method comprises: step S1, in an inert atmosphere, adding an initiator dropwise into an acrylamide solution to obtain a mixed aqueous solution of polyacrylamide; step S2, adding a precipitation aid into the mixed aqueous solution, and drying and grinding the precipitated solid in sequence to obtain polyacrylamide powder; step S3, dissolving the polyacrylamide powder into a first solvent to obtain an intermediate solution, adding tannic acid to the intermediate solution, and stirring for a certain period of time under ice bath conditions to obtain a composite binder having a three-dimensional cross-linked network structure.

[0008] Furthermore, step S1 comprises: adding acrylamide monomer into the second solvent to obtain an acrylamide solution.

[0009] Further, in step S1, in the reactants, the mass ratio of acrylamide monomer to the second solvent is (3.0-8.0): (30.0-60.0).

[0010] Furthermore, in step S3, in the reactants, the mass ratio of the polyacrylamide powder, the first solvent, and tannic acid is (1.0-3.0): (25.0-75.0): (1.0-3.0).

[0011] Further, step S1 includes: step S11, introducing an inert gas into a container containing acrylamide solution for a certain period of time; step S12, under the conditions of introducing an inert atmosphere and the solution temperature being within a first temperature range, adding an initiator dropwise for polymerization to obtain a mixed aqueous solution of polyacrylamide; wherein the inert atmosphere or inert gas is preferably nitrogen.

[0012] Furthermore, the initiator is ammonium persulfate, and / or the precipitation aid is anhydrous ethanol.

[0013] Furthermore, the first temperature range is 35°C-45°C.

[0014] Further, after adding tannic acid to the intermediate solution, step S3 comprises:

[0015] Under the condition of introducing an inert atmosphere and an ice bath at 0°C to 4°C, stirring is performed for 8 to 12 hours to obtain a composite adhesive.

[0016] Furthermore, the negative electrode sheet includes a composite binder, and the composite binder is prepared by the above-mentioned preparation method.

[0017] Furthermore, the lithium battery includes a negative electrode sheet, and the negative electrode sheet is the negative electrode sheet mentioned above.

[0018] In an embodiment of the present invention, an initiator is added dropwise to an acrylamide solution in an inert atmosphere to obtain a mixed aqueous solution of polyacrylamide, a precipitating agent is added to the mixed aqueous solution to obtain polyacrylamide powder, the polyacrylamide powder is dissolved in a first solvent to obtain an intermediate solution, tannic acid is added to the intermediate solution, and after stirring for a certain period of time under ice bath conditions, a composite binder having a three-dimensional cross-linked network structure is obtained. The prepared novel binder has the advantages of rich polar functional groups and a 3D cross-linked network, has excellent adhesion and high tensile properties, can effectively adapt to the volume expansion of the silicon-based negative electrode, ensures the integrity of the electrode, and ensures higher performance of the battery, thereby solving the technical problem in the prior art that the volume expansion of the silicon-based negative electrode cannot be well buffered due to poor adhesion and tensile strength of the binder. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0020] Figure 1 A preparation flow chart of an embodiment of a method for preparing a composite cross-linking adhesive according to the present invention is shown;

[0021] Figure 2 A comparison chart of the cycle performance of different binder samples prepared in Example 2 and Comparative Examples 1-2 at 0.2C is shown;

[0022] Figure 3 A schematic diagram of the rate performance of different binder samples prepared in Examples 1-3 and Comparative Examples 1-2 is shown. DETAILED DESCRIPTION

[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0024] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0025] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein, for example. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0026] Now, exemplary embodiments according to the present application will be described in more detail with reference to the accompanying drawings. However, these exemplary embodiments may be implemented in a variety of different forms and should not be construed as being limited to the embodiments described herein. It should be understood that these embodiments are provided to make the disclosure of the present application thorough and complete, and to fully convey the concepts of these exemplary embodiments to those of ordinary skill in the art. In the accompanying drawings, for the sake of clarity, the thickness of the layers and regions may be enlarged, and the same reference numerals are used to represent the same devices, and thus their descriptions will be omitted.

[0027] Silicon-based anode is a battery structure that uses silicon material as the anode. Silicon has high specific capacity and abundant resources, so it is widely studied for use in the battery field. Silicon-based anode has higher energy density and cycle stability in lithium-ion batteries, which can improve the performance and cycle life of the battery. However, silicon-based anode also faces problems such as capacity expansion and large volume changes, which need to be solved by designing a reasonable structure and coating materials. With the continuous advancement of technology, silicon-based anode is expected to become an important component of the next generation of high energy density batteries.

[0028] Tannic acid is a class of naturally occurring organic compounds, mainly found in plants, such as grapes, tea leaves, oak, etc. It is a polyphenolic compound with multiple phenolic hydroxyl groups, and therefore has strong antioxidant properties. Tannic acid, as a polyhydroxy-rich annular tree-like structure, is a modifier that forms a three-dimensional cross-linked network structure binder with polyacrylamide. On the one hand, it provides abundant polar groups that can form hydrogen bonds with the surface of the silicon-based negative electrode. On the other hand, the three-dimensional network structure formed has better adhesion and high tensile strength, which can well buffer the volume expansion of the silicon-based negative electrode and ensure the integrity of the electrode structure, thereby ensuring better electrochemical performance of the battery. Tannic acid also has the following chemical properties:

[0029] 1. Acidity: Tannic acid is a weak acid, and its acidity mainly comes from its phenolic hydroxyl groups. These phenolic hydroxyl groups can release protons, making tannic acid acidic.

[0030] 2. Oxidizing property: Tannic acid has strong oxidizing property and can react with oxygen to form products with antioxidant properties.

[0031] 3. Chelating property: Tannic acid can form complexes with metal ions, which have a certain effect on inhibiting oxidation reactions caused by metals.

[0032] 4. Reducing property: Tannic acid has certain reducing property and can participate in some reduction reactions, reacting with oxygen or other oxidants to produce reduction reactions.

[0033] Combination Figures 1 to 3As shown, according to a specific embodiment of the present application, a method for preparing a composite binder for a silicon-based negative electrode is provided, and the preparation method comprises:

[0034] Step S1, in an inert atmosphere, adding an initiator (ammonium persulfate) dropwise into an acrylamide solution to obtain a mixed aqueous solution of polyacrylamide;

[0035] A certain mass of monomer acrylamide (AM) was weighed and placed in a three-necked flask, and a certain amount of deionized water was added to dissolve it to obtain an aqueous solution of acrylamide (the mass ratio of acrylamide monomer to deionized water was (3.0-8.0): (30.0-60.0)). First, nitrogen was introduced for 30 minutes to remove residual oxygen in the flask to prevent the occurrence of side reactions; then, under nitrogen protection and 40°C, an initiator of ammonium persulfate was added dropwise to polymerize for 4-8 hours to obtain a mixed aqueous solution of polyacrylamide.

[0036] Ammonium persulfate is a commonly used initiator with the following advantages: 1. High efficiency: ammonium persulfate releases highly efficient active oxygen free radicals when initiating the reaction, which can quickly initiate the reaction and accelerate the reaction speed; 2. Safety: ammonium persulfate is relatively safe compared to other initiators and is not prone to explosion or other accidents; 3. Stability: ammonium persulfate is easy to store and carry, is not easily affected by the external environment, and has high stability; 4. Easy to use: ammonium persulfate is easily soluble in water, easy to use, and can be used as an initiator in an aqueous system; 5. Controllability: By controlling the concentration of ammonium persulfate and the reaction conditions, the speed and effect of the initiation reaction can be controlled.

[0037] In the above steps, the components and reactant contents are shown in the following table (by mass):

[0038]

[0039] Step S2, adding a precipitation aid to the mixed aqueous solution, drying and grinding the precipitated solid in sequence to obtain polyacrylamide powder; adding anhydrous ethanol for precipitation until no white solid precipitates, drying the precipitated white solid under infrared or the like, and then grinding to obtain pure polyacrylamide powder.

[0040] Using anhydrous ethanol as a precipitation aid has the following advantages:

[0041] 1. Anhydrous ethanol is a common organic solvent with high solubility. It can effectively dissolve many organic substances and is conducive to the precipitation of target substances;

[0042] 2. Anhydrous ethanol is non-toxic to most biological molecules, has little effect on biological samples, and can maintain the biological activity of the samples;

[0043] 3. Anhydrous ethanol is easy to evaporate and can be easily removed from the solution, which is beneficial for subsequent experimental steps;

[0044] 4. Anhydrous ethanol is cheap, easy to obtain, and has low cost;

[0045] 5. Anhydrous ethanol is relatively stable, easy to control and simple to operate in experimental operation. The precipitated solid is placed under infrared and other conditions for drying.

[0046] The advantages of infrared drying are as follows: 1. Quick drying: Infrared drying technology can quickly evaporate the moisture on the surface of objects, making the objects dry quickly; 2. Energy saving and environmental protection: Infrared drying technology can accurately control the heating area, reduce energy waste, improve energy utilization, and save energy and protect the environment; 3. Uniform drying: Infrared drying technology can evenly heat the surface of objects to avoid local overheating or overcooling, and ensure that the objects are dry as a whole; 4. Wide range of applications: Infrared drying technology is suitable for objects of various materials and shapes; 5. Simple operation: Infrared drying equipment is simple to operate, easy to maintain, and reduces labor costs; 6. Improve production efficiency: Infrared drying technology has a fast drying speed, which can improve production efficiency and shorten the production cycle.

[0047] Step S3, placing polyacrylamide powder (PAM) in a round-bottom flask and adding deionized water to dissolve it, weighing an appropriate amount of tannic acid (TA) in the round-bottom flask, stirring for 8-12 hours under nitrogen protection and 0-4°C ice bath conditions to obtain a cross-linked adhesive TA@PAM (i.e., a composite adhesive). The mass ratio of polyacrylamide powder, the first solvent (deionized water), and tannic acid is (1.0-3.0): (25.0-75.0): (1.0-3.0).

[0048] In an embodiment of the present invention, an initiator is added dropwise to an acrylamide solution in an inert atmosphere to obtain a mixed aqueous solution of polyacrylamide, a precipitating agent is added to the mixed aqueous solution to obtain polyacrylamide powder, the polyacrylamide powder is dissolved in a first solvent to obtain an intermediate solution, tannic acid is added to the intermediate solution, and after stirring for a certain period of time under ice bath conditions, a composite binder having a three-dimensional cross-linked network structure is obtained. The prepared novel binder has the advantages of rich polar functional groups and a 3D cross-linked network, has excellent adhesion and high tensile properties, can effectively adapt to the volume expansion of the silicon-based negative electrode, ensures the integrity of the electrode, and ensures higher performance of the battery, thereby solving the technical problem in the prior art that the volume expansion of the silicon-based negative electrode cannot be well buffered due to poor adhesion and tensile strength of the binder.

[0049] Furthermore, step S1 comprises: adding acrylamide monomer into the second solvent to obtain an acrylamide solution.

[0050] Further, in step S1, in the reactants, the mass ratio of acrylamide monomer to the second solvent is (3.0-8.0): (30.0-60.0).

[0051] Furthermore, in step S3, in the reactants, the mass ratio of the polyacrylamide powder, the first solvent, and tannic acid is (1.0-3.0): (25.0-75.0): (1.0-3.0).

[0052] Further, step S1 includes: step S11, introducing an inert gas into a container containing acrylamide solution for a certain period of time; step S12, under the conditions of introducing an inert atmosphere and the solution temperature being within a first temperature range, adding an initiator dropwise for polymerization to obtain a mixed aqueous solution of polyacrylamide; wherein the inert atmosphere or inert gas is preferably nitrogen.

[0053] Furthermore, the initiator is ammonium persulfate, and / or the precipitation aid is anhydrous ethanol.

[0054] Furthermore, the first temperature range is 35°C-45°C.

[0055] Further, after adding tannic acid to the intermediate solution, step S3 comprises:

[0056] Under the condition of introducing an inert atmosphere and an ice bath at 0°C to 4°C, stirring is performed for 8 to 12 hours to obtain a composite adhesive.

[0057] Furthermore, the negative electrode sheet includes a composite binder, and the composite binder is prepared by the above-mentioned preparation method.

[0058] Furthermore, the lithium battery includes a negative electrode sheet, and the negative electrode sheet is the negative electrode sheet mentioned above.

[0059] Specifically, the negative electrode sheet includes a composite binder, and the composite binder is prepared by the preparation method of the above embodiment.

[0060] Specifically, the lithium battery includes a negative electrode sheet, and the negative electrode sheet is a negative electrode sheet using the above-mentioned composite binder.

[0061] The following is further described by experimental examples.

[0062] [Example 1]:

[0063] This embodiment prepares a modified conductive adhesive composite material, and the specific steps are as follows:

[0064] 1) 4.0 g of monomer acrylamide (AM) was weighed and placed in a three-necked flask, and 36.0 g of deionized water was added to dissolve to obtain an aqueous solution of acrylamide with a concentration of 10%. First, nitrogen was introduced for 30 minutes to remove residual oxygen in the flask to prevent the occurrence of side reactions; then, nitrogen was continuously introduced for protection, and at 40° C., an initiator of ammonium persulfate was added dropwise to polymerize for 6 hours to obtain a mixed aqueous solution of polyacrylamide, and then anhydrous ethanol was added for precipitation until no white solid was precipitated, and the precipitated white solid was placed under infrared drying, etc., and then ground to obtain pure polyacrylamide powder.

[0065] 2) Weigh 2.0g of PAM prepared in step 1 and place it in a round-bottom flask, add 50.0g of deionized water to dissolve it, weigh 2.0g of TA in the round-bottom flask, stir for 12h under nitrogen protection and 0-4℃ ice bath conditions to obtain the cross-linking binder TA@PAM1. According to the added mass of different substances, calculate the mass fraction of the modified substance to prepare for the subsequent preparation of button battery pole piece slurry. For example, the mass fraction of the binder at this time is: 2*2 / (2+2+50)=7.41%.

[0066] According to the mass ratio of 80:10:10, 2.4g of silicon negative electrode material, 0.3g of conductive carbon, and 0.3g of cross-linked binder composite material (TA@PAM1) prepared in Example 1 were weighed respectively (i.e., the mass of the glue solution was 0.3 / 7.41%=2.049g) and placed in a ball mill, and slowly ball milled for 5 minutes for pre-dissolution. After pre-dissolution, it can be observed whether deionized water needs to be added to the slurry according to the consistency of the slurry. After accelerating the ball milling speed for 30 minutes of homogenization, the slurry of the silicon negative electrode is obtained. The ball-milled slurry is coated on copper foil, and cut into circular pole pieces with a diameter of 12mm after vacuum drying at 105°C. After drying, the mass of the pole pieces is accurately weighed and the content of active substances is calculated. Metal lithium sheets are used as counter electrodes and Celgard 2400 is used as diaphragms to assemble button cells in a vacuum glove box.

[0067] [Example 2]:

[0068] The preparation process of PAM and TA@PAM is the same as that of Example 1. The preparation process of the cross-linking binder only needs to change the mass ratio of TA to PAM to 2:1. At this time, the modified conductive binder is named TA@PAM2. The subsequent process is also the same as that of Example 1.

[0069] [Example 3]:

[0070] The preparation process of PAM and TA@PAM is the same as that of Example 1. The preparation process of the cross-linking binder only needs to change the mass ratio of TA to PAM to 3:1. At this time, the modified conductive binder is named TA@PAM3. The subsequent process is also the same as that of Example 1.

[0071] [Comparative Example 1]:

[0072] According to the mass ratio of 80:10:10, 1.2g of silicon negative electrode material, 0.15g of conductive carbon, and 0.15g of PAA (PAA is a pre-prepared aqueous solution with a mass fraction of 5%, that is, the mass of the glue weighed is 0.15 / 5% = 3g) are weighed and placed in a ball mill, and slowly ball milled for 5 minutes for pre-dissolution. After pre-dissolution, it can be observed whether deionized water needs to be added to the slurry according to the consistency of the slurry. After accelerating the ball milling speed for 30 minutes of homogenization, the silicon negative electrode slurry is obtained. The ball-milled slurry is coated on copper foil, and cut into circular pole pieces with a diameter of 12mm after vacuum drying at 105°C. After drying, the mass of the pole piece is accurately weighed and the active material content is calculated. Metal lithium sheets are used as counter electrodes and Celgard 2400 is used as diaphragms to assemble button cells in a vacuum glove box.

[0073] [Comparative Example 2]:

[0074] The process is the same as that of comparative example 1, except that PAA is replaced by CMC. (Note: CMC is a 5% aqueous solution prepared in advance, that is, the mass of the glue solution weighed is 0.15 / 5%=3g).

[0075] Performance test results analysis:

[0076] Depend on Figure 3 It can be seen from the rate performance that the rate performance of the samples using the binder of Examples 1-3 is much better than that of the samples using the binder of Comparative Examples 1-2. The reason for this is that PAA, as a polymer material with a linear structure, not only has a limited degree of adhesion to the electrode material, but also has a relatively single channel for the conduction of ions / electrons to the electrode; CMC has the problem of high brittleness and poor elasticity, and will cause powder loss in the early stage of the production of the electrode, and the electrode material will fall off faster under the impact of different current cycles; while the three-dimensional network formed by TA@PAM not only provides effective adhesion, but also provides abundant channels for the transmission of ions / electrons and shortens the transmission distance to the greatest extent. Among them, the sample of Example 2 is better than that of Examples 1 and 3, because the amount of TA added in Example 1 is less, and the three-dimensional network formed is less; while in Example 3, excessive addition of TA will hinder the structure itself from transmitting lithium ions and reduce the adhesion to the electrode material.

[0077] Depend on Figure 2It can be seen from the cycle performance of the preferred embodiment 2 binder that the sample cycle performance of this sample is much better than the sample using the binder of comparative example 1-2. The reason for this is that PAA has a certain bonding strength as a binder, but due to its linear structure, the silicon particles continue to expand and contract as the cycle progresses, causing the electrode material to fall off from the current collector;

[0078] Because CMC is brittle and has poor elasticity, when it is used as a binder, the negative electrode will experience structural collapse and severe powder loss during the pressing and slitting process, resulting in rapid capacity decay. TA@PAM2 not only has excellent bonding strength, but also its three-dimensional network can better coat and bond the electrode material in all directions, so that it can better withstand the expansion of silicon particles during the recycling process to ensure the stability of the electrode structure, thereby enhancing the cycle life of the battery.

[0079] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0080] 1. A tannic acid-crosslinked polyacrylamide silicon-based negative electrode binder is prepared by crosslinking tannic acid with polyacrylamide, wherein the binder has the advantages of rich polar functional groups and a 3D crosslinked network;

[0081] 2. The binder has excellent adhesion and high tensile properties, which can effectively adapt to the volume expansion of the silicon-based negative electrode, ensure the integrity of the electrode, and ensure higher performance of the battery.

[0082] For ease of description, spatially relative terms such as "above", "above", "on the upper surface of", "above", etc. may be used here to describe the spatial positional relationship between a device or feature and other devices or features as shown in the figure. It should be understood that spatially relative terms are intended to include different orientations of the device in use or operation in addition to the orientation described in the figure. For example, if the device in the accompanying drawings is inverted, the device described as "above other devices or structures" or "above other devices or structures" will be positioned as "below other devices or structures" or "below other devices or structures". Thus, the exemplary term "above" can include both "above" and "below". The device can also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatially relative descriptions used here are interpreted accordingly.

[0083] In addition to the above, it should be noted that "one embodiment", "another embodiment", "embodiment", etc. mentioned in this specification refer to the specific features, structures or characteristics described in conjunction with the embodiment included in at least one embodiment generally described in this application. The same expression appearing in multiple places in the specification does not necessarily refer to the same embodiment. Further, when describing a specific feature, structure or characteristic in conjunction with any embodiment, it is claimed that the realization of such feature, structure or characteristic in conjunction with other embodiments also falls within the scope of the present invention.

[0084] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite binder for a silicon-based negative electrode, characterized in that: The preparation method comprises: Step S1, in an inert atmosphere, adding an initiator dropwise into an acrylamide solution to obtain a mixed aqueous solution of polyacrylamide; Step S2, adding a precipitation aid to the mixed aqueous solution, and drying and grinding the precipitated solid in sequence to obtain polyacrylamide powder; Step S3, dissolving the polyacrylamide powder in a first solvent to obtain an intermediate solution, adding tannic acid to the intermediate solution, and stirring the solution in an ice bath for a certain period of time to obtain a composite adhesive having a three-dimensional cross-linked network structure.

2. The preparation method according to claim 1, characterized in that: The step S1 comprises: The acrylamide monomer is added to the second solvent to obtain an acrylamide solution.

3. The preparation method according to claim 2, characterized in that: In step S1, in the reactants, the mass ratio of the acrylamide monomer to the second solvent is (3.0-8.0): (30.0-60.0).

4. The preparation method according to claim 1, characterized in that: In step S3, in the reactants, the mass ratio of the polyacrylamide powder, the first solvent, and the tannic acid is (1.0-3.0): (25.0-75.0): (1.0-3.0).

5. The preparation method according to claim 1, characterized in that: Step S1 includes: Step S11, introducing an inert gas into a container containing the acrylamide solution for a certain period of time; Step S12, under the condition that the inert atmosphere is introduced and the solution temperature is within the first temperature range, the initiator is added dropwise for polymerization to obtain a mixed aqueous solution of the polyacrylamide; Wherein, the inert atmosphere or the inert gas is preferably nitrogen.

6. The preparation method according to claim 1 or 5, characterized in that: The initiator is ammonium persulfate, and / or the precipitation aid is anhydrous ethanol.

7. The preparation method according to claim 5, characterized in that: The first temperature range is 35°C-45°C.

8. The preparation method according to claim 1, characterized in that: After adding tannic acid to the intermediate solution, step S3 comprises: Under the conditions of introducing an inert atmosphere and an ice bath at 0° C. to 4° C., stirring is performed for 8 to 12 hours to obtain the composite adhesive.

9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a composite binder, and the composite binder is prepared by the preparation method according to any one of claims 1 to 8.

10. A lithium battery, characterized in that: The lithium battery comprises a negative electrode sheet, and the negative electrode sheet is the negative electrode sheet according to claim 9.